(untitled) (Journal of Hama University, 2024)
The current study aimed at assessment of bacterial pollution of cows (calves) and laminated surfaces in the stores of Homs, and the extent to which meat are matched with germans and standards, where samples were taken from the surfaces of cows (calves) Sold for bacterial examination within June 2022 by taking 20 samples of meat shops in the form of 5 cm2 swabs of meat surfaces for sale from the shoulder area and 70 samples of the surfaces and carried out tests The bacterial census included (census of live bacteria, enumeration of colon germs and census of coli, the enumeration of golden clusters and detection of salmonia germs). The results of this study showed that the proportion of positive samples for the existing TVBC live germs are (100%) in cows meat, where the average number of Live CFU / cm2 is 3.7x107, and the results of a bacteria The colon is also high, with its existence (95%) and average CFU / cm2 1.3x105, the result of the presence of Emerianest Coli bacteria (75%) and average 2.2x103 CFU / cm2, and as The results showed the presence of golden cluster, 70% and 4.7x104 CFU / cm2, and the number of positive samples for the presence of salmonella germs (1/20) was a presence (5%). The results also showed that most of the study samples were made with the standard specifications of the Syrian standing where the total violation of the total vulnerability of live bacteria (10) at a rate (50%) and the number of samples violated healthy for salmonia (1) At a rate of 5%.